Role of dislocations in nitride laser diodes with different indium content - Agata Bojarska-Cieślińska (Nature Portfolio, 2021)
Abstract In this work we investigate the role of threading dislocations in nitride light emitters with different indium composition. We compare the properties of laser diodes grown on the low defect density GaN substrate with their counterparts grown on sapphire substrate in the same epitaxial process. All structures were produced by metalorganic vapour phase epitaxy and emit light in the range 383–477 nm. We observe that intensity of electroluminescence is strong in the whole spectral region for devices grown on GaN, but decreases rapidly for the devices on sapphire and emitting at wavelength shorter than 420 nm. We interpret this behaviour in terms of increasing importance of dislocation related nonradiative recombination for low indium content structures. Our studies show that edge dislocations are the main source of nonradiative recombination. We observe that long wavelength emitting structures are characterized by higher average light intensity in cathodoluminescence and better thermal stability. These findings indicate that diffusion path of carriers in these samples is shorter, limiting the amount of carriers reaching nonradiative recombination centers. According to TEM images only mixed dislocations open into the V-pits, usually above the multi quantum wells thus not influencing directly the emission.